Review of Company 1 (Maarten van Regteren Altena, Derek Bailey, Tristan Honsinger, Evan Parker) and Company 2 (Derek Bailey, Anthony Braxton, Evan Parker) - Barry, Malcolm (Contact: A Journal for Contemporary Music (1971-1990), 1978)